Common Fixed Point Theorem for Three Self-maps in \(G_{JS}\)-Metric Space - Srilatha, D.; Kiran, V. (Communications in Mathematics and Applications, 2024)
In this article, we prove a common fixed point theorem for three self-maps using the contractive modulus function in a recently emerged generalized metric space known as \(G_{JS}\)-metric space and verified its uniqueness. We illustrated the main theorem with an example.